THE EFFECT OF INTERNAL COMMUNICATION, RESPONSIBILITY, AND WORK LOYALTY ON EMPLOYEE PERFORMANCE - Riski Ulan Sari; Januar Eky Pambudi (ZILLZELL MEDIA PRIMA, 2024)
This study aims to determine the influence of Internal Communication, Responsibility, and Loyalty on Employee Performance at Daar-Huda Islamic Boarding School. The sample of this study amounted to 60 respondents with a descriptive approach using quantitative methods, with the help of SPSS software version 26. Sampling using saturated sampling techniques using the entire population as a sample. The results showed that: 1) Internal Communication has a positive and significant effect on Employee Performance. 2) Responsibility has a positive and significant effect on Employee Performance. 3) Work Loyalty has a positive and significant effect on Employee Performance. 4) Internal Communication, Responsibility and Work Loyalty have a positive and significant effect on employee performance. The implications of this study show that Internal Communication, Responsibility and Work Loyalty can improve Employee Performance at Daar El-Huda Islamic Boarding School.